Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1101/2020.03.11.986364
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Axillary Microbiota Compositions from Men and Women in a Tertiary Institution-South East Nigeria: Effects of Deodorants/Antiperspirants on Bacterial Communities

Abstract: 14The axillary skin microbiota compositions of African populations that live in warm climate is not 15 well studied with modern next-generation sequencing methods. To assess the microbiota 16 compositions of the axillary region of healthy male and female students, we used 16S rRNA 17 metagenomics method and clustered the microbial communities between those students that 18 reported regular use of deodorants/antiperspirants and those that do not. Axillary skin swab was 19 self-collected by 38 male and 35 fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…Body malodor is the most common reason humans generally use deodorants or antiperspirants in order to obtain an appealing body odor or to mask and reduce sweat from the apocrine glands of the skin. In our previous study, 7 we observed that the relative abundance of Corynebacterium (68.06% vs 42.40%) was higher in those that reported regular use of deodorants. Thus, suggesting that the use of deodorants/antiperspirants facilitates the proliferation of Corynebacterium species as high levels of strong body odor were observed by Taylor et al 22 …”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Body malodor is the most common reason humans generally use deodorants or antiperspirants in order to obtain an appealing body odor or to mask and reduce sweat from the apocrine glands of the skin. In our previous study, 7 we observed that the relative abundance of Corynebacterium (68.06% vs 42.40%) was higher in those that reported regular use of deodorants. Thus, suggesting that the use of deodorants/antiperspirants facilitates the proliferation of Corynebacterium species as high levels of strong body odor were observed by Taylor et al 22 …”
Section: Discussionmentioning
confidence: 60%
“…Our study group lately demonstrated that Corynebacterium (53.89%) was the most relative abundant genera in males, followed by Staphylococcus (19.66%), Anaerococcus (4.91%) and Cutibacterium (1.21%), while in females Corynebacterium (50.17%) was the most relative abundant genera, followed by Staphylococcus (20.90%), Anaerococcus (7.51%), Acinetobacter (2.79%), Propionibacterium (1.84%), Enhydrobacter (1.68%), Micrococcus (1.64%), Finegoldia (1.47%), and Peptoniphilus (1.08%) 7 …”
Section: Introductionmentioning
confidence: 99%